A paradox of apparent brainless behavior: The time-course of compound word recognition. (July 2019) - Schmidtke, Daniel; Kuperman, Victor
Abstract: A review of the behavioral and neurophysiological estimates of the time-course of compound word recognition brings to light a paradox whereby temporal activity associated with lexical variables in behavioral studies predates temporal activity of seemingly comparable lexical processing in neuroimaging studies. However, under the assumption that brain activity is a cause of behavior, the earliest reliable behavioral effect of a lexical variable must represent an upper temporal bound for the origin of that effect in the neural record. The present research provides these behavioral bounds for lexical variables involved in compound word processing. We report data from five naturalistic reading studies in which participants read sentences containing English compound words, and apply a distributional technique of survival analysis to resulting eye-movement fixation durations (Reingold & Sheridan, 2014). The results of the survival analysis of the eye-movement record place a majority of the earliest discernible onsets of orthographic, morphological, and semantic effects at less than 200 ms (with a range of 138–269 ms). Our results place constraints on the absolute time-course of effects reported in the neurolinguistic literature, and support theories of complex word recognition which posit early simultaneous access of form and meaning.